AKIBAT HUKUM WANPRESTASI TERHADAP PERJANJIAN JUAL-BELI ATAS HASIL PERKEBUNAN JERUK DI DESA MANGGUH KECAMATAN KINTAMANI KABUPATEN BANGLI - I Kadek Darmana Adi Putra; Ratna Artha Windari; Dantes, Komang Febrinayanti; Kusuma, Putu Riski Ananda (Universitas Pendidikan Ganesha, 2025)
This research aims (1) to find out and analyze the legal consequences of default in sales and purchase agreements for orange plantation products in Mangguh Village, Kintamani District, Bangli Regency. (2) to find out and analyze what legal remedies can be taken in the event of a breach of contract in the sale and purchase agreement for the orange plantation harvest in Mangguh Village, Kintamani District, Bangli Regency. The type of research used by researchers is empirical legal research, which is qualitative in nature with research locations in Mangguh Village, Kintamani, Bangli. The data sources in this research are primary data from interviews, secondary data from statutory regulations, journals, articles, literature and scientific papers that are relevant to the main problem being studied. Data collection techniques in this research were carried out using observation, document study and interviews. The sampling technique used is the Non-Probability Sampling technique and the subject | 2 determination uses the Purposive Sampling technique. Data processing and analysis techniques are used qualitatively. The results of the research show that (1) the legal consequences that arise from the default that occurs are losses on the part of the farmer as the seller, therefore the seller has the right to demand that the performance be fulfilled in accordance with the provisions of Article 1267 of the Civil Code, along with compensation for the losses suffered. by the seller in accordance with the provisions of Article 1243 of the Civil Code. (2) Legal efforts can be classified into two forms, namely litigation and non-litigation. However, based on the conditions in the field, legal remedies that can be taken by the aggrieved seller include negotiations, mediation, and filing a lawsuit in court.